Sejarah Desa Saentis Periode 1920-2010 - Saragih, Aldi Trinata; Tanjung, Flores; Marpaung , Herman Parjuangan; br Sinuhaji , Soniya; Pangaribuan , Yulia Artha (Innovative: Journal Of Social Science Research, 2025)
Village or udik according to universal definition is an agglomeration of settlements in rural areas. In Indonesia, the term village is a division of administrative areas under subdistricts that are under the leadership of the village head. Furthermore, the village is also referred to as a unitary legal community that has territorial boundaries that have the authority to regulate and take care of the interests of the local community based on local origins and customs that are recognized and respected in the system of government of the Unitary State of the Republic of Indonesia. In its development, saentis village exists because of the influx of foreigners to Indonesia, especially the Dutch who opened tobacco plantations in Deli Serdang. The Dutch who came under the leadership of JC. Van Houten. Tobacco plantations continue to grow and fall under dutch society.Saentis village community is a multicultural society, it can be seen from the life of saentis village community, where the population is able to create a life without conflict, mutual tolerance with other ethnicities. The current state of Saentis village is inseparable from the changing dynamics of Saentis villagers. Population dynamics is the change or growth of population numbers over time, caused by birth, death, population displacement